Critical process parameters optimization for hyperthermostable Î² amylase production by Bacillus subtilis DJ5 using response surface methodology - doi: 10.4025/actascibiolsci.v36i1.17427 (Acta Scientiarum. Biological Sciences, 2013)
The combined effects of significant physical and chemical factors affect hyperthermostable Î² amylase production under submerged fermentation by Bacillus subtilis DJ5. The above was studied using the experimental design and response surface methodology. A 23 full-factorial central composite design was chosen to analyze interactions among three factors i.e. substrate concentration, medium pH and incubation temperature. The experimental data were fitted into a polynomial model for the yield of enzyme and an optimum level was arrived at with optimized conditions. Solving the coded values using Excel equation function indicated that maximum enzyme production is possible at a substrate concentration of 7.07 mg mL-1, pH 6.622 and temperature of 35.435°C. Such prediction was validated with practical experiments in which, at the prescribed condition maximum yield of 15.62 U mg-1, nearly 1.5 fold higher than non-optimized condition was observed.